2013
DOI: 10.1109/mpe.2013.2268814
|View full text |Cite
|
Sign up to set email alerts
|

All Options on the Table: Energy Systems Integration on the Island of Maui

Abstract: Beach: ©iStockphoto.com/marcopolo9442 people: ©ShutterStock.com/DeniS criSto E EnErgy systEms intEgration in thE hawaiian island of maui is unique because of the island's high renewable energy (rE) penetration, advanced adoption of plug-in vehicles, distributed power generation, and isolated island electrical system. Currently, a large amount of wind power produced on maui is curtailed because the power cannot be accommodated by the existing power grid. analysis of changes in electrical grid operations to redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Sometimes, the wind power is so abundant that electricity generation from wind needs to be curtailed as it would overwhelm the power grid. This situations has been investigated in the study [18], which summarized the results of integrating RERs into the power grid. The study [18] also investigated the synergistic effects of EV penetration, RER integration, and methods to store generated renewable energy.…”
Section: A Projects Considering Integration Of Rers Into the Sgmentioning
confidence: 99%
“…Sometimes, the wind power is so abundant that electricity generation from wind needs to be curtailed as it would overwhelm the power grid. This situations has been investigated in the study [18], which summarized the results of integrating RERs into the power grid. The study [18] also investigated the synergistic effects of EV penetration, RER integration, and methods to store generated renewable energy.…”
Section: A Projects Considering Integration Of Rers Into the Sgmentioning
confidence: 99%
“…Integrated modelling revealed that curtailed energy dropped from 23.1% to 19.0% by utilising a smart charging option. In the best case simulated for the year 2030, delivered variable renewable energy reached 26.4% of the total energy delivered [21].…”
Section: Introductionmentioning
confidence: 97%
“…In order to reduce its fossil fuel dependence, the US Department of Energy set a goal of achieving 40% of renewable generation by 2030 [21]. Integrated modelling revealed that curtailed energy dropped from 23.1% to 19.0% by utilising a smart charging option.…”
Section: Introductionmentioning
confidence: 99%
“…In New Zealand, where the RE was the 38% of primary energy in 2010 and biomass, the solar thermal energy supplied the 20% of the energy produced. Maui Island, November 2012, had a 16 MW electricity generation plant from sugar-cane bagasse, providing the 4.5% of the Island energy [143]. In the Island of Crete, there is a 166 kW biogas plant combined with another RETs.…”
Section: Renewable Energy Sources On Islandsmentioning
confidence: 99%